1970
DOI: 10.1080/00173137009427394
|View full text |Cite
|
Sign up to set email alerts
|

Spore Morphology and Taxonomy of Polypodiaceae

Abstract: Pal, Sunanda and I'd, N. (Dept. Dot., Government College, Darjeeling, West Bengal, India.) Spore ttiorphology arid foxoriortiy of Polypodiaceae. Grana 10: 141-148, illus., 1970.-The examination of spores belonging to eight species reprcscnting five genera of Polypodiaceae reveals that they are typically free, anisopolar and monolete (bilateral). In a majority of cases the sporcs are yellow and have a short Iaesura-about half the length of the greater equatorial axis of the spore. Generally, the spores arc elli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Several features, including the presence of specialized sterile fronds, rhizome growth-form, the distance between adjacent phyllopodia, the insertion type of rhizome scales, scale margin morphology, stomata type, venation type, sori arrangement, indumenta shape and epispore ornamentation, were all treated as diagnostic characters for infrageneric classification and species delimitation of Pyrrosia s.l. in previous studies 2 – 4 , 6 , 8 , 20 , 22 – 24 , 31 , 61 , 69 . If we only use morphologic characters to evaluate the infrageneric classification in Pyrrosia s.l., most groups or sections are not monophyletic 4 , 25 .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Several features, including the presence of specialized sterile fronds, rhizome growth-form, the distance between adjacent phyllopodia, the insertion type of rhizome scales, scale margin morphology, stomata type, venation type, sori arrangement, indumenta shape and epispore ornamentation, were all treated as diagnostic characters for infrageneric classification and species delimitation of Pyrrosia s.l. in previous studies 2 – 4 , 6 , 8 , 20 , 22 – 24 , 31 , 61 , 69 . If we only use morphologic characters to evaluate the infrageneric classification in Pyrrosia s.l., most groups or sections are not monophyletic 4 , 25 .…”
Section: Discussionmentioning
confidence: 58%
“…Confluent sori and orbicular and discrete sori have been treated as the diagnostic character even at the species and genus level in Polypodiaceae 69 72 . Coenosori was be considered as one of the main characters to separate the previous genus Drymoglossum from Pyrrosia s.l., although some authors considered this classification “purely artificial” 69 . The homoplasy of confluent sori in Pyrrosia s.l.…”
Section: Discussionmentioning
confidence: 99%
“…Spore data were compiled by incorporating the results of previously published studies (Bosman 1991 ; Dai et al 2006 ; Devi 1981 ; Hennipman 1990 ; Huang 1981 ; Jiang et al 2010 ; Kholia et al 2012 ; Large and Braggins 1991 ; Large et al 1992 ; Mitui 1971 1977 ; Nayar and Devi 1964 ; Nooteboom 1997 ; Pal and Pal 1970 ; Qi and Zhang 2009 ; Rödl-Linder 1990 1994 ; Shalimov et al 2013 ; Shi 2002 ; Shi and Zhang 1998 ; Sugong et al 2005 ; Tryon and Lugardon 1991 ; van Uffelen 1993 ; Wang 2001 ; Zhang et al 2006 ; Zink 1993 ) and novel observations partially based on the MSc thesis of the first author (Chen 2011 ). Spore samples were obtained from specimens recently collected in Taiwan, and from herbarium specimens of the National Sun Yat-Sen University of Taiwan (SYSU), and Taiwan Forestry Research Institute (TAIF).…”
Section: Methodsmentioning
confidence: 99%
“…The measurement of spore size was based on 15 grains. The determination of spore characteristic followed the definition of Erdtman (1957), Nayar & Devi (1964), Pal & Pal (1970), Regalado & Sanchez (2002), Lashin (2012) and Wei & Dong (2012). Common.…”
Section: Palynological Studymentioning
confidence: 99%
“…The spore study of Aspleniaceae members had been reported on Asplenium from India (Nayar & Devi 1964), Cuba (Regalado & Sanchez 2002), Saudi Arabia (Lashin 2012), China (Wei & Dong 2012) and Java (Indonesia) (Pranita et al 2017). While spore studies of Polypodiaceae had been reported on Genera Phymatodes, Microsorium, Crypsonus, Lepisorus and Campyloneurum from India (Pal & Pal 1970). Morbelli & Giudice (2010) also reported the spore morphology of Polypodiaceae, genera Campyloneurum, Microgramma, Pecluma, Phlebodium, Pleopeltis and Serpocaulum from Argentina.…”
Section: Identification Keymentioning
confidence: 99%